Red notice : a true story of high finance, murder, and one man's fight for justice - Browder, Bill, 1964- (Simon & Schuster, 2015)
"A real-life political thriller about an American financier in the Wild East of Russia, the murder of his principled young tax attorney, and his dangerous mission to expose the Kremlin's corruption"--Amazon.com.